Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/nl301748m
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of MnO2/Mn/MnO2 Sandwich-Structured Nanotube Arrays with High Supercapacitive Performance for Electrochemical Energy Storage

Abstract: We demonstrate the design and fabrication of novel nanoarchitectures of MnO(2)/Mn/MnO(2) sandwich-like nanotube arrays for supercapacitors. The crystalline metal Mn layers in the MnO(2)/Mn/MnO(2) sandwich-like nanotubes uniquely serve as highly conductive cores to support the redox active two-double MnO(2) shells with a highly electrolytic accessible surface area and provide reliable electrical connections to MnO(2) shells. The maximum specific capacitances of 937 F/g at a scan rate of 5 mV/s by cyclic voltamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
263
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(269 citation statements)
references
References 52 publications
3
263
0
3
Order By: Relevance
“…Nevertheless, the thickness and the area-normalized capacitance of these electrodes are not adequate for most applications. A promising approach to realize practical applications of MnO 2 is to incorporate nanostructured MnO 2 on highly conductive support materials with high surface areas such as nickel nanocones (13), Mn nanotubes (14), activated carbon (15), carbon fabric (16), conducting polymers (17), carbon nanotubes (18,19), and graphene (20)(21)(22)(23)(24). Although promising…”
mentioning
confidence: 99%
“…Nevertheless, the thickness and the area-normalized capacitance of these electrodes are not adequate for most applications. A promising approach to realize practical applications of MnO 2 is to incorporate nanostructured MnO 2 on highly conductive support materials with high surface areas such as nickel nanocones (13), Mn nanotubes (14), activated carbon (15), carbon fabric (16), conducting polymers (17), carbon nanotubes (18,19), and graphene (20)(21)(22)(23)(24). Although promising…”
mentioning
confidence: 99%
“…The specific capacitance of the electrodes with different scan rates is given in Figure 4b. Specific capacitance of the electrode was calculated by integrating the voltammetric charge in the CV curves 18. At the same scan rate, the resulting specific capacitance for the multi‐shelled Mn 2 O 3 hollow microspheres electrodes were much higher than that of the Mn 2 O 3 NPs, and among them triple‐shelled Mn 2 O 3 hollow microspheres achieved a maximum capacitance, the crest value of specific capacitance of 1640 F g –1 at the scan rate of 5 mV s –1 can be achieved with the triple‐shelled Mn 2 O 3 hollow microspheres.…”
mentioning
confidence: 99%
“…It is suggested that the unique architectures of the highly conductive Mn layer and the double hallow nanostructured MnO 2 have provided large surface area and short ion di®u-sion path that contribute to the high capacitive performance. 85 On top of their poor electronic conductivity, the electrochemical cyclability is another important issue for MnO 2 electrodes. 52 Zhang et al achieved promising result from MnO 2 /PANI composites with the maximum speci¯c capacitance of 320 F/g compared to that of pure MnO 2 (125 F/g).…”
Section: Manganese Oxide (Mno 2 )-Based Compositesmentioning
confidence: 99%